Analisis Wanprestasi Pada Perjanjian Kerjasama Investasi Pembuatan Pabrik Mie Dan Bihun: (Studi Atas Putusan Nomor 98/Pdt.G/2019/PN Mlg) - Lale Sundari Djolo Puri; Zaenal Arifin Dilaga (Fakultas Hukum Universitas Mataram, 2023)
The aims of this research are to know judge’ consideration in declared breach of contract in cooperation agreement in the investment of noodles and rice noodles factory and its legal consequences as stated in the Verdict of Malang District Court Number 98/Pdt.G/2019/PN Mlg. This research applied normative legal research. Result’ of this study shows that judge’ consideration in declare the case as stated in the Malang District Court Verdict, according to the opinion of expert witnesses in breach of contract and statement and evidences of the plaintiff. The legal consequences rise from this case, defendant has to pay compensation to the plaintiff and court fee.